2010
DOI: 10.1021/ja102194x
|View full text |Cite
|
Sign up to set email alerts
|

Donor−Acceptor Biomorphs from the Ionic Self-Assembly of Porphyrins

Abstract: Microscale four-leaf clover-shaped structures are formed by self-assembly of anionic and cationic porphyrins. Depending on the metal complexed in the porphyrin macrocycle (Zn or Sn), the porphyrin cores are either electron donors or electron acceptors. All four combinations of these two metals in cationic tetra(N-ethanol-4-pyridinium)porphyrin and anionic tetra(sulfonatophenyl)porphyrin result in related cloverlike structures with similar crystalline packing indicated by X-ray diffraction patterns. The clover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
110
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 44 publications
2
110
0
Order By: Relevance
“…In the field of self-assembly, the assembled structures also present the feature of diversity [13][14][15]. A slight change of assembling condition makes the structures of products totally different [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of self-assembly, the assembled structures also present the feature of diversity [13][14][15]. A slight change of assembling condition makes the structures of products totally different [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…We found that much more of 3 must have been desorbed according to the UV-vis spectra of the released porphyrins. Normally, the mixing of cationic and anionic porphyrins is forms 1:1 mixtures [19,25]; cyclic voltammery has suggested this to be the case for our system also (vide infra), demonstrating that the desorption of the different porphyrins is solvent dependant. In the case of 1/3-SWNT, almost equimolar amounts of 1 and 3 were obtained from the stripping of the SWNTs.…”
Section: Resultsmentioning
confidence: 64%
“…In particular, the combination of a cationic and an anionic porphyrin leads to a very high loading (>200 nmol per mg SWNT) through electrostatic interactions. This system can be regarded as a supramolecular extended co-operative binary ionic (CBI) solid [19]; these materials are of high interest in electronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Even if the formation of dimers or trimers of porphyrins is principally described, it is interesting to mention the work of Shelnutt and coworkers who have obtained original electrostatic self-assembled multi-porphyrin nanostructures. [9][10][11][12] Indeed, depending on the central metal (Zn or Sn), the porphyrins are either electron donors or electron acceptors, respectively, and thus nanotubes and clover-shaped nanostructures can be formed (see Figures 2A and 2B).…”
Section: Introductionmentioning
confidence: 99%